TOA-Based Relative Localization With Reflecting Signal Paths Assisted: Algorithm and Performance Analysis - Zhang, Zhibo; Chang, Qing; Zhao, Na; Wang, Hao (IEEE sensors letters, 2022)
This letter investigates a communication node relative localization problem based on time-of-arrival (TOA), where both the distances in direct signal paths and reflecting signal paths are measured. A wireless sensor network model of distance measurements and node locations is established, and a new two-step localization iterative algorithm is proposed. Simulation results illustrate the performance of the proposed algorithm, which is compared with Cramer-Rao lower bounds (CRLBs) and genetic algorithm (GA)-based algorithms.